Practical Course of Basic English: Analytical Reading and Conversation - (:unkn) unknown (Технодрук, 2025)
The teaching manual on Analytical Reading and Oral Communication offers a comprehensive set of tasks and exercises aimed at developing students’ communicative competence and coherent speech skills. The materials focus on fostering the effective use of dialogic and monologic forms of communication, as well as on systematizing and expanding learners’ vocabulary. The proposed activities promote the development of analytical reading skills and support meaningful oral interaction in academic contexts. The manual is intended for first-year students of the Faculty of Foreign Languages who study English as their first foreign language.
Навчальний посібник з аналітичного читання та усного мовлення містить комплекс завдань та вправ спрямованих на розвиток комунікативних навичок когерентного мовлення, використання сформованих діалогічних та монологічних компетенцій на систематизацію і розширення словникового запасу. Запропонований посібник призначено для студентів першого курсу факультету іноземних мов, що вивчають англійську мову як першу іноземну.